Hibriditas Aluk Todolo dan Kekristenan Dalam Ritual Ma’bulle Tomate Di Gandangbatu: Hibriditas Aluk Todolo dan Kekristenan Dalam Ritual Ma’bulle Tomate Di Gandangbatu - Ones Kristiani Rapa' (Melo: Jurnal Studi Agama-agama, 2021)
This paper aims to see the cultural hybridity in the beliefs of Aluk Todolo and Christianity that occurs in the Ma'bulle Tomate Rite in Gandangbatu. This rite is one part of a series of the most famous traditional ceremonies in Toraja, namely Rambu Solo'. Ma'bulle Tomate was initially accompanied by badong in Aluk Todolo but later accompanied by singing in Christianity. In this paper the author uses qualitative research methods through data collection observations and interviews. The theory of Homi K. Baba in a book entitled The Location Of Culture is the theory that the author chooses to dissect the problems that occur. The theory says that cultural hybridity is the third space that should be a discursive space because through this there has been a violation of spatial boundaries that signifies a contradiction of objects, uses, meanings, spaces and properties in a tradition. Through the results of the study, it was found that Aluk Todolo used badong as a mourning poem in the Ma'bulle Tomate ritual and Christianity used spiritual songs. In addition, the meaning of badong and singing were also found . Among other things: lifting and telling the social status of the deceased, the expectations of the community and the worship of spirits. Through this theory, it is concluded that cultural hybridity    Aluk Todolo and Christianity in the Ma'bulle Tomate ritual in Gandangbatu are the starting point for the beautiful encounter between the two cultures. Two different cultures, namely between Aluk Todolo and Christianity, meet in the Ma'bulle Tomate rite.   Tulisan ini bertujuan untuk melihat hibriditas budaya dalam kepercayaan Aluk Todolo dan Kekristenan yang terjadi dalam Ritus Ma’bulle Tomate di Gandangbatu. Ritus ini merupakan salah satu bagian dalam rangkaian upacara adat yang paling terkenal di Toraja yaitu Rambu Solo’. Ma’bulle Tomate awalnya diiringi dengan badong dalam Aluk Todolo namun kemudian diiringi dengan nyanyian dalam kekristenan. Dalam tulisan ini penulis menggunakan metode penelitian kulitatif melalui pengumpulan data observasi dan wawancara. Teori dari Homi K. Baba dalam buku yang berjudul The Location Of Culture menjadi teori yang dipilih penulis untuk membedah masalah yang terjadi. Teori tersebut mengatakan bahwa hibriditas budaya merupakan ruang ke tiga   yang seharusnya menjadi ruang diskursif karena melalui hal ini telah terjadi pelanggaran batas ruang yang menandakan suatu kontradivisi dari objek, penggunaan, makna, ruang dan properti dalam suatu tradisi. Melalui hasil penelitian, ditemukan bahwa Aluk Todolo menggunakan badong sebagai syair duka dalam ritual Ma’bulle Tomate dan kekristenan menggunakan nyanyian rohani. Selain itu ditemukan juga makna badong dan nyanyian. Antara lain: mengangkat dan menceritakan status sosial dari orang yang telah meninggal, pengharapan dari masyarakat dan pemujaan kepada arwah. Melalui teori tersebut disimpulkan bahwa hibriditas budaya Aluk Todolo dan kekristenan dalam ritual Ma’bulle Tomate Di Gandangbatu merupakan titik tolak perjumpaan yang indah antara dua kebudayaan tersebut. Dua kebudayaan yang berbeda yakni antara Aluk Todolo dan kekeristenan berjumpa dalam ritus Ma’bulle Tomate.